Surveying Support for the Integrated Development of Resources of Mining Regions - Yuldashovich, Sokhibov Isomiddin; Abdishukurovich, Korabaev Husniddin (European Journal of Life Safety and Stability (2660-9630), 2021)
For the integrated development of the subsoil, a method has been developed that allows to significantly increase the efficiency of mining reserves under water bodies and prevent negative consequences for the environment. The essence of this method consists in the fact that lava is worked out directly under the water body in the safety tselik, the parameters of which are calculated so that through-water cracks connecting the river with the mine workings are not formed in the rock thickness.